‘Sustainability in our DNA’ - Jaayna, Jeevita (Star Media Group Berhad, 2025)
SUSTAINABILITY is part of the identity and way of life at Universiti Sains Malaysia (USM), says Prof Datuk Dr Abdul Rahman Mohamed.